Globalization, Outsourcing and Labour Development in ASEAN - Chalamwong, Yongyuth (Asian Journal of Applied Economics, 2016)
“Thangavelu and Chongvilaivan provide interesting insights and useful implications for labour and industrial development in the context of an emerging global hub of outsourcing market, the ASEAN.”